2019
DOI: 10.1039/c9ra00509a
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of phenol by catalytic wet air oxidation: a comparative study of copper and nickel supported on γ-alumina, ceria and γ-alumina–ceria

Abstract: Influence of the calcination and reduction treatment effects used to activate catalysts on the global catalytic performance on phenol oxidation over different supports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 97 publications
1
12
0
1
Order By: Relevance
“…On the other hand, alumina catalysts with a Cu content of 5 %, similar to those shown here, have been used in the CWAO of the phenol at 3 hours of reaction describing its catalytic behavior both in the oxidized state and in the reduced state, where better catalytic behavior occurs in the first case. However, the incorporation of a third element such as 5 % Ce in the alumina interacting with the same Cu content improves twice the activity in the phenol CWAO, both in the oxidized and reduced state in the catalyst . This turns out to be as relevant as what happened in the 90′s when Striolo et al used three different homogeneous catalysts (Fe−Cu−Mn) in the CWAO of organic acids, which showed that the synergy between the three metals considerably improves the activity in comparison when only two or one catalysts was used in the system .…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…On the other hand, alumina catalysts with a Cu content of 5 %, similar to those shown here, have been used in the CWAO of the phenol at 3 hours of reaction describing its catalytic behavior both in the oxidized state and in the reduced state, where better catalytic behavior occurs in the first case. However, the incorporation of a third element such as 5 % Ce in the alumina interacting with the same Cu content improves twice the activity in the phenol CWAO, both in the oxidized and reduced state in the catalyst . This turns out to be as relevant as what happened in the 90′s when Striolo et al used three different homogeneous catalysts (Fe−Cu−Mn) in the CWAO of organic acids, which showed that the synergy between the three metals considerably improves the activity in comparison when only two or one catalysts was used in the system .…”
Section: Resultsmentioning
confidence: 76%
“…However, the incorporation of a third element such as 5 % Ce in the alumina interacting with the same Cu content improves twice the activity in the phenol CWAO, both in the oxidized and reduced state in the catalyst. [44] This turns out to be as relevant as what happened in the 90's when Striolo et al used three different homogeneous catalysts (FeÀ CuÀ Mn) in the CWAO of organic acids, which showed that the synergy between the three metals considerably improves the activity in comparison when only two or one catalysts was used in the system. [45] The above described leaves us with important evidence so that soon this type of catalysts can interact as shown here, with other elements or oxides that synergistically can significantly improve the activity in the CWAO.…”
Section: Resultsmentioning
confidence: 97%
“…The trimetallic supported nanocatalysts developed and synthesized in this study possess particular structural properties allowing them to be used for several catalytic applications. The close intimate interaction between metals and support (strong metal–support interaction) is a highly desirable structural property for nanocatalysts as it promotes their redox properties [ 53 , 54 ]. The strong metal–support interaction has a relationship with the number of oxygen vacancies in the support [ 54 , 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…The close intimate interaction between metals and support (strong metal–support interaction) is a highly desirable structural property for nanocatalysts as it promotes their redox properties [ 53 , 54 ]. The strong metal–support interaction has a relationship with the number of oxygen vacancies in the support [ 54 , 55 , 56 ]. CeO 2 has attracted much interest in the oxidation process due to its high oxygen storage capacity and unique redox ability.…”
Section: Resultsmentioning
confidence: 99%
“…Catalytic wet air oxidation (CWAO) is one of the most economical and environmentally friendly wastewater treatment technologies used to break down organic matters into a more easily biodegradable form. CWAO has been used for the treatment of refractory organic pollutants, such as carboxylic acids and phenolic compounds (e.g., bisphenol A, BPA) [1][2][3]. The CWAO process can be efficiently conducted under mild operating conditions (low temperature and pressure) owing to the performance of heterogeneous catalysts [4][5][6].…”
Section: Introductionmentioning
confidence: 99%